VD_FINDINFO HC / 2013 / 166 vom 1. März 2013 - VD Tribunal cantonal (2013)
OBLIGATION D'ENTRETIEN, CONJOINT, UNION CONJUGALE, RÉTROACTIVITÉ, DÉPENS | 173 al. 3 CC, 176 al. 1 ch. 1 CC, 106 al. 1 CPC (CH)